Reformulation of National Defense Policy Based on Artificial Intelligence Technology for Decision-Making - Ghazalie Ghazalie; Yusuf Ali; Aris Sarjito; Bambang Kustiawan; Asep Adang Supriyadi; Ceppi Hilmansyah; Wisnu Saputro; Katherine Erika (Jurnal Ilmiah Global Education, 2026)
The integration of Artificial Intelligence (AI) into national defense strategy has emerged as a pivotal necessity amid increasing geopolitical tensions, cyber threats, and the evolution of modern warfare. This essay explores the reformulation of national defense policy in Indonesia by leveraging AI technologies to enhance strategic decision-making, operational effectiveness, and national security resilience. Through a qualitative-descriptive approach, the study highlights how AI contributes to intelligence analysis, military simulation, autonomous weapons systems, and cyber defense infrastructure. However, the integration of AI also presents complex challenges, including cybersecurity vulnerabilities, ethical dilemmas related to autonomous decision-making in combat, and the lack of standardized international regulations. The study underscores the need for comprehensive policy reform that balances technological innovation with adherence to humanitarian and international law. Drawing upon global case studies—from the European Union’s strategic autonomy initiatives to Nordic operational cooperation and post-Brexit UK-EU security dynamics—the paper identifies best practices and policy gaps. Key recommendations include strengthening cyber defense systems, developing ethical oversight mechanisms, improving regulatory clarity, and fostering international cooperation on AI governance in defense. Furthermore, the research emphasizes the importance of human-centered AI deployment and the development of skilled military personnel capable of managing AI-based systems. The findings support the necessity for Indonesia to adopt an adaptive, ethical, and collaborative AI defense policy that aligns with global norms while preserving national sovereignty and security. This reformulation ensures that AI becomes not just a tool of modernization, but a strategic asset that enhances both the deterrent and responsive capacities of the state in an increasingly uncertain global security environment.